The Impact of Ambivalence of Article 14 of the PTPK Law on the Eradication of Corruption - Aminudin J. Dunggio; Dian Ekawty Ismail; Erman I. Rahim (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The purpose of this writing is to analyze Article 14 of Law Number 31 of 1999 jo. Law Number 20 of 2001 concerning the Eradication of Corruption has a delegative character, because its enactment depends on the provisions of other laws that expressly declare a violation as a criminal act of corruption. The construction of these norms in practice gives rise to ambivalence in law enforcement, especially when various acts that are detrimental to state finances occur in strategic sectors that are not explicitly qualified as corruption crimes in sectoral laws. This condition has the potential to create a legal vacuum and hinder the effectiveness of eradicating corruption as an extraordinary crime. This study aims to analyze the practice of implementing Article 14 of the Law on the Eradication of Corruption and examine these provisions from the perspective of legal certainty, justice, and criminal law policy. The research method used is normative legal research with a legislative approach and a case approach. Research data was obtained through literature studies on primary, secondary, and tertiary legal materials that were analyzed qualitatively. The results of the study show that the delegative and limiting nature of Article 14 has implications for the low predictability of the law and opens up ambivalence between norms and law enforcement practices. In reality, law enforcement officials often apply the Corruption Crime Law to acts that are normatively outside the scope of Article 14, taking into account the existence of state financial losses and the interests of substantive justice. Therefore, Article 14 needs to be interpreted systemically and progressively and supported by the reformulation of norms and harmonization of laws and regulations to be in line with the dynamics and complexity of modern corruption crimes.